Optimal management of renal artery fibromuscular dysplasia - Gottsäter A; Lindblad B (Dove Medical Press, 2014)
Anders Gottsäter, Bengt Lindblad Department of Vascular Diseases, Skåne University Hospital, Malmö, Sweden Abstract: Fibromuscular dysplasia (FMD) is a nonatherosclerotic, noninflammatory angiopathy of unknown cause affecting medium-sized (most commonly renal) arteries and causing renovascular hypertension. The most common medial multifocal type of FMD (with the “string of beads” appearance) is more than four times more prevalent in females than in males. FMD accounts for up to 10% of cases of renovascular hypertension. Compared with patients with atherosclerotic renal artery stenosis, patients with FMD are younger, have fewer risk factors for atherosclerosis, and a lower occurrence of atherosclerosis in other vessels. The etiology is multifactorial, including vessel wall ischemia and smoking, as well as hormonal and genetic factors. Intra-arterial digital subtraction angiography is still the gold standard for exclusion or confirmation of renal artery stenosis caused by FMD, at least in young patients, who more often have lesions in branches of the renal artery. For FMD patients with atherosclerosis and those who are older (>50–55 years), significant renal artery stenosis may be confirmed or excluded with ultrasonography. The FMD lesion is typically truncal or distal, whereas atherosclerotic lesions are more often proximal or ostial. Treatment options are medical, endovascular (percutaneous transluminal renal angioplasty [PTRA]), and surgical. Invasive treatment should be considered when hypertension cannot be controlled with antihypertensive drugs and in patients with impaired renal function or ischemic nephropathy. PTRA has become the treatment of choice and normally yields good results, especially in unifocal disease and young patients. Pressure gradients are normally completely abolished, and there is no indication for stent placement. Surgical revascularization is indicated after PTRA complications; thrombosis, perforation, progressive dissection, repeated PTRA failure or restenosis. Centralization of handling is recommended. Keywords: fibromuscular dysplasia, renal artery stenosis, arterial hypertension, percutaneous transluminal renal angioplasty, renal artery surgery